Immigrants Are Like ... The Representation of Immigrants in Italy: The Metaphors Used by Students and Their Family Backgrounds - Elisa Cavicchiolo; Fabio Alivernini; Sara Manganelli (LED Edizioni Universitarie, 2016)
The aim of this study is to identify the way young Italian students represent immigrants and to evaluate the existence of relationships between these representations and the family background of the students. The data is based on a sample of Italian students (N = 841). The respondents were given an open question, which asked them to provide a simile or a metaphor concerning immigrants. A mixed methodology was employed, which involved: (i) analysis of the qualitative content; (ii) quantitative analysis investigating the relationship between the categories identified by means of an analysis of the content and the socioeconomic status of the student. The results showed a very diverse and articulated set of representations, with the contents of the metaphors produced by the students ranging from those based on a kind of «us-them» opposition, to images based on an attitude of tolerance and equality, and semantic regions with a more emotional component. The analysis revealed some statistically significant relationships between the socio-economic backgrounds of the students' families and some types of metaphors produced by the students. The mixed research methodology adopted proved to be effective with respect to the objectives of the study, and it combines the use of reliable statistical tools with the qualitative richness of metaphor-based answers to open questions.